Implementation of differentiated learning in the Kurikulum Merdeka in class IV - Fajri Anuar; Febrina Dafit (Inovasi Kurikulum)
Differentiated learning is learning that accepts and acknowledges readiness and interest in learning so that student learning diversity occurs. The aim of carrying out a differentiated approach is to ensure that students receive an approach that suits their characteristics and needs to maximize their potential and motivate them to learn. This research uses a qualitative approach in its methodology. The instruments used were interviews, observation, and documentation. Triangulation is a data validation technique that compares or checks the correctness of data using sources other than the original data. The validity of the data in this research uses three triangulations: technique, source, and time triangulation. Data and data sources were obtained through observation, documentation, and interviews. Primary data in this research are teachers and school principals. Meanwhile, secondary data used in this research was collected from various sources, including books, journals, papers, and other supporting materials. The results of the study concluded that there are several stages in differentiated learning, namely mapping students' needs through diagnostic assessments, designing differentiated learning plans according to students' needs by implementing content, process, and product strategies, and evaluating and reflecting on the learning that has been implemented.